Adaptive leadership in a global economy : perspective for application and scholarship - Raei, Mohammed, 1974-; Rasmussen, Harriette Thurber, 1954- (New York, NY : Routledge, 2022)
"With the entire world experiencing the global pandemic and its aftermath, VUCA (Volatile, Uncertain, Complex, and Ambiguous) conditions have never been more extreme and the need for adaptive leadership never more urgent. But how is adaptive leadership applied outside Western cultures? How can it be taught through leadership development programs? Which tools enhance its practice and its teaching? How does adaptive leadership relate to other key theories and practices? This volume answers these questions and more as it illustrates how adaptive leadership practices address some of the world's most pressing challenges-political and cultural division, remote work, crisis management-across a variety of sectors. Adaptive leadership has been explained as a key leadership approach for dealing with adaptive, as distinguished from technical or predictable, problems, especially prevalent in complex environments. However, adaptive leadership scholarship has suffered from a lack of conceptual clarity and casual application of its core concepts. It remains solidly Western in its prescriptions. This book will expand readers' understanding of adaptive leadership and its potential to solve local and global adaptive challenges and will explore its relevance and application to cultures outside the United States. Aiming to increase conceptual clarity about adaptive leadership to enhance future scholarship and application and illustrate novel approaches and perspectives, this book will be of interest to researchers, academics, practitioners, and students in the fields of leadership, strategy, and organizational studies"--
Keywords: Leadership; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning